2020
DOI: 10.1111/jcmm.15498
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin ameliorates caerulein‐induced chronic pancreatitis by inhibiting the activation of PSCs and pancreatic infiltration of macrophages

Abstract: Chronic pancreatitis (CP) is characterized by persistent inflammation of the pancreas that results in progressive loss of the endocrine and exocrine compartment owing to atrophy and/or replacement with fibrotic tissue. Currently, the clinical therapeutic scheme of CP is mainly symptomatic treatment including pancreatic enzyme replacement, glycaemic control and nutritional support therapy, lacking of specific therapeutic drugs for prevention and suppression of inflammation and fibrosis aggravating in CP. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…In immunofluorescence, iNOS and CD206 were used to mark M1 and M2 macrophages, respectively. In quantitative real-time PCR, the markers of M1 ( Inos, Cd86, Il-12a , and Tnf-α ) and M2 ( Cd163, Cd206 , and Ym-1 ) macrophages were consistent with previous studies [ 6 , 30 , 42 45 ]. Compared with the control group (Con), conditioned medium from WT and Mlkl -/- mouse-derived, PBS-treated pancreatic acinar cells (CM-WT-PBS, CM- Mlkl -/- -PBS) exhibited weak pro-M1 ability, although significant differences were found only in CD86 and YM-1 mRNA levels (Fig.…”
Section: Resultssupporting
confidence: 90%
“…In immunofluorescence, iNOS and CD206 were used to mark M1 and M2 macrophages, respectively. In quantitative real-time PCR, the markers of M1 ( Inos, Cd86, Il-12a , and Tnf-α ) and M2 ( Cd163, Cd206 , and Ym-1 ) macrophages were consistent with previous studies [ 6 , 30 , 42 45 ]. Compared with the control group (Con), conditioned medium from WT and Mlkl -/- mouse-derived, PBS-treated pancreatic acinar cells (CM-WT-PBS, CM- Mlkl -/- -PBS) exhibited weak pro-M1 ability, although significant differences were found only in CD86 and YM-1 mRNA levels (Fig.…”
Section: Resultssupporting
confidence: 90%
“…In addition, ILG weakens the M1 polarization trend of macrophages by affecting the NF-κB signaling pathway, but does not affect M2 polarization. The above experimental results suggest that ILG is a candidate drug for CP worthy of further study ( 88 ).…”
Section: Research Progress Of Anti-inflammatory and Anti-fibrotic The...mentioning
confidence: 89%
“…Furthermore, recent studies showed that multiple miRs (miR-301, miR-200c, miR-149, miR-139, miR-34b) can affect the activity of PSCs during chronic pancreatitis, and modulation of their levels leads to PSCs apoptosis [ 70 , 71 , 72 , 73 , 74 ]. Moreover, studies demonstrated that targeting PSCs with antifibrotic or anti-inflammatory compounds in a form of siRNA or small molecules could prevent chronic pancreatitis progression [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. YAP1 has been shown to induce the activity of PSCs and stimulate pancreatic fibrosis during chronic pancreatitis [ 83 ].…”
Section: Discussionmentioning
confidence: 99%